Customary Offenses and Their Sanctions in Indonesia: Analysis of Bengkulu City Regional Regulation No. 29 of 2003 and Rejang Lebong Regency Regional Regulation No. 5 of 2018 - Toha Andiko; Khairuddin Khairuddin (Jurnal Madania)
This research aims to describe the advantages and disadvantages of customary regulations in the city of Bengkulu and Rejang Lebong district, as well as to provide alternative solutions for the improvement of customary regulations so that they are not overlapping with higher regulations and can be deeper in absorbing the laws that live in society, without neglecting justice, expediency, and legal certainty applicable in Indonesia. This research is included in the form of normative juridical research. This type of research is qualitative. The approach used in this research is a statutory approach (statue approach). As a result, the implementation of customary law in Bengkulu city with regard to customary violations has gone quite well, for example in the case of Cempalo Tangan in the form of stealing or damaging (article 21 of Bengkulu City Regional Regulation No. 29 of 2003). Whereas in Rejang Lebong, it has also worked well, for example in other serious cempalo cases such as killing (article 25 of Rejang Lebong Regency Perda No.5 of 2018). In the review of Islamic law, sanctions for customary violations that occur in Bengkulu city are generally not contrary to Islamic law, and are in line with the principle of zawajir. In the review of positive law in Indonesia, the punishment for thieves with customary fines in the form of apologies, compensation, and performing the traditional ceremony of tepung Setawar Sedingin, this is contrary to article 362 which stipulates a maximum prison sentence of 5 years, and if accompanied by violence/threats, shall be sentenced to a maximum imprisonment of 9 years (Article 365 of the Indonesian Penal Code).